Relevance of Trick (Makar) in Hashtag #2019GantiPresiden - Faridah, Siti (Law Research Review Quarterly, 2018)
The dynamics of the general election events that took place in Indonesia caused the Indonesian state to have a low quality democracy, ranking 68 out of 167 countries, still inferior to Timor Leste which was ranked 48. Democracy is a view of life that prioritizes equality. In general democracy in Indonesia is flawed democracy, characterized by free and fair elections and respect for civil liberties, but has significant weaknesses in governance, a political culture that is not too healthy, and a low level of political participation. It won't be long before the general elections (elections) in Indonesia take place in 2019. Long before that there was a movement called # 2019GantiPresiden which has been heating up lately. A tense situation between the two has the potential to lead to the commotion that will occur. Inaccuracies occur among the political elites behind them. # 2019GantiPresiden was responded by the opposition with another hashtag that was written # Jokowi2Periode. Politics that occurred long before the nomination of a candidate by the election commission caused conditions in the community to heat up. Jokowi's supporters call the # 2019GantiPresiden movement an attempted rebellion against legitimate government while in other opposition it calls violations of democratic freedom (as happened in the new order era).